(untitled) - Levi, Primo (New York, 1995)
First published in English in 1965, "The Reawakening" is Primo Levi's bestselling sequel to his classic memoir of the Holocaust, "Survival in Auschwitz." The inspiring story of Levi's liberation from the German death camp in January 1945 by the Red Army, it tells of his strange and eventful journey home to Italy by way of the Soviet Union, Hungary, and Romania. Levi's railway travels take him through bombed-out cities and transit camps, with keen insight he describes the former prisoners and Russian soldiers he encounters along the way. An extraordinary account of faith, hope, and undying courage, "The Reawakening" was praised by Irving Howe as "a remarkable feat of literary craft."
Keywords: Người Do Thái,Jews; Tiểu sử,Biography; Nước Ý,Italy